2000
DOI: 10.3152/147154300781781841
|View full text |Cite
|
Sign up to set email alerts
|

Science and governance in the European Union: a contribution to the debate

Abstract: .N auka i S zko ln ic tw o W y żs ze " 1 /1 9 /2 0 0 2 Silvio Funtowicz, lain Shepherd, David Wilkinson, Jerry Ravetz Nauka i proces rządzenia w Unii Europejskiej -gtos w dyskusji1Aspekty naukowe decyzji podejmowanych na szczeblu Unii Europejskiej, dotyczących kwestii adm inistracyjnych lub zasad prowadzonej polityki, budzą coraz większe zainteresowanie. Pewne cechy tego procesu -w tym potencjalnie nieodwracalne skutki podejm owanych decyzji, wiążąca się z nimi niepewność oraz presja skłaniająca naukowców do w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 11 publications
0
23
0
2
Order By: Relevance
“…Instead, in sustainability research, critiques of the top-down model of knowledge transfer and patriarchalcolonial paradigm of corresponding capacity building as 'banking concepts' (Freire, 1970), 'deficit models' (Lewenstein, 2002;Wynne, 1991) and 'neocolonial science' (Dahdouh-Guebas et al, 2003) have gained currency. Consequently, increasing attention has been given to interactive ways of producing knowledge, conceived of as a basic requirement in research for sustainable development Rist et al, 2006;Pregernig, 2006;Guggenheim, 2006;Maasen and Lieven, 2006;Robinson and Tansey, 2006;Cundill et al, 2005;Lawrence and Després, 2004;Kasemir et al, 2003;Ravetz, 2001;Klein et al, 2001;Funtowicz et al, 2000).…”
mentioning
confidence: 99%
“…Instead, in sustainability research, critiques of the top-down model of knowledge transfer and patriarchalcolonial paradigm of corresponding capacity building as 'banking concepts' (Freire, 1970), 'deficit models' (Lewenstein, 2002;Wynne, 1991) and 'neocolonial science' (Dahdouh-Guebas et al, 2003) have gained currency. Consequently, increasing attention has been given to interactive ways of producing knowledge, conceived of as a basic requirement in research for sustainable development Rist et al, 2006;Pregernig, 2006;Guggenheim, 2006;Maasen and Lieven, 2006;Robinson and Tansey, 2006;Cundill et al, 2005;Lawrence and Després, 2004;Kasemir et al, 2003;Ravetz, 2001;Klein et al, 2001;Funtowicz et al, 2000).…”
mentioning
confidence: 99%
“…New approaches to the use of scientific knowledge in the policy process Funtowicz et al (2000) identified several elements in which policy-related science, which they also called precautionary science, differs from normal science. These differences concern the products delivered and the process for generating and applying the knowledge.…”
Section: Conclusion and Comparison With Other Casesmentioning
confidence: 99%
“…A basic assumption of this model is that through the generation of scientific knowledge, the uncertainty about the problem under consideration is reduced, and information becomes available that can be used as a basis for political decision-making, for the justification of decisions taken and for the fine-tuning and implementation of decisions (Wettestad and Andresen, 1990). Several alternative models for generating and applying scientific knowledge in environmental policy and management have been proposed, requiring amongst others, broadening the range of scientific disciplines, involving stakeholders and making scientific advice more salient, credible and legitimate (Collingridge and Reeve, 1986;Brooks, 1987;Nowotny, 1987;Jasanoff, 1990;Funtowicz and Ravetz, 1993;Funtowicz et al, 2000;Collins and Evans, 2002;Cash et al, 2003;Nowotny, 2005;Lentsch and Weingart, 2012). Central in most of these alternative models is the bridging of the gap between the scientific and political realms through translation, integration, selection, aggregation, evaluation, assessment and transfer of scientific knowledge, often taking place within specific structures at the interface of the scientific and policy communities.…”
Section: Introductionmentioning
confidence: 99%
“…Discussions can no longer remain restricted to the traditional circle of researchers from one's own discipline. There is a need for 'extended peer review' (Funtowicz and Ravetz 1993;Funtowicz et al 2000).…”
Section: Changing Position Of Expertsmentioning
confidence: 99%